Menciptakan Habitus Moderasi Beragama: Upaya Pondok Pesantren Sunan Pandanaran dalam Meneguhkan Islam Rahmatan Lil ‘Alamin - Muharis, Muharis (Islam & Contemporary Issues, 2023)
This research is important to do considering that currently Indonesia and even the world need a moderation model of religion as a solution for the emergence of various fundamentalist ideas that lead to acts of radicalism and terrorism in a plural-multi-religious-multicultural society. The main problem which is the object of study in this study is the form of internalization of religious moderation carried out by the Sunan Pandanaran Islamic Boarding School which is unique and unique. This study uses a sociological approach with the theory used is Pierre Bourdieu's "habitus" theory, the concept of habitus is used to raise public opinion about habits (habit). The findings from this research are that the Sunan Pandanaran Islamic Boarding School as an object of study is able to apply the values ??of religious moderation. This is of course not only manifested through the curriculum in Islamic boarding schools but becomes a habitus (culture) within it. Pondok Pesantren Sunan Pandanaran is also able to apply an inclusive model of religious moderation, for example by becoming a meeting place for interfaith communities to organize various activities related to religious moderation, both on a local, national and international scale. Of course this is interesting because the students are not only fed with theories of religious moderation, but are also confronted directly with the reality of an interfaith community so that students can find out what attitude is shown when dealing directly with them (people of different religions) in order to uphold the mission of Islam Rahmatan Lil' Alamin.